Stochastic Thresholds: A Novel Explanation of Nonlinear Dose-Response Relationships for Stochastic Radiobiological Effects - Bobby R. Scott PhD (SAGE Publishing, 2005)
New research data for low-dose, low- linear energy transfer (LET) radiation-induced, stochastic effects (mutations and neoplastic transformations) are modeled using the recently published NEOTRANS 3 model. The model incorporates a protective, stochastic threshold (StoThresh) at low doses for activating cooperative protective processes considered to include presumptive p53-dependent, high-fidelity repair of nuclear DNA damage in competition with presumptive p53-dependent apoptosis and a novel presumptive p53-independent protective apoptosis mediated (PAM) process which selectively removes genomically compromised cells (mutants, neoplastic transformants, micronucleated cells, etc.). The protective StoThresh are considered to fall in a relatively narrow low-dose zone (Transition Zone A). Below Transition Zone A is the ultra-low-dose region where it is assumed that only low-fidelity DNA repair is activated along with presumably apoptosis. For this zone there is evidence for an increase in mutations with increases in dose. Just above Transition Zone A, a Zone of Maximal Protection (suppression of stochastic effects) arises and is attributed to maximal cooperation of high-fidelity, DNA repair/apoptosis and the PAM process. The width of the Zone of Maximal Protection depends on low-LET radiation dose rate and appears to depend on photon radiation energy. Just above the Zone of Maximal Protection is Transition Zone B, where deleterious StoThresh for preventing the PAM process fall. Just above Transition Zone B is a zone of moderate doses where complete inhibition of the PAM process appears to occur. However, for both Transition Zone B and the zone of complete inhibition of the PAM process, high-fidelity DNA repair/apoptosis are presumed to still operate. The indicated protective and deleterious StoThresh lead to nonlinear, hormetic-type dose-response relationships for low-LET radiation-induced mutations, neoplastic transformation and, presumably, also for cancer.